Promotora outreach, education and navigation support for HPV vaccination to Hispanic women with unvaccinated daughters - Parra-Medina, Deborah (J Cancer Educ, 2015)
BACKGROUND: Cervical cancer disparities persist in the predominantly Hispanic population of South Texas, and Hispanic girls are less likely to initiate and complete the three-dose HPV vaccine series. Culturally relevant interventions are needed to eliminate these disparities and improve HPV vaccine initiation and completion. SUBJECTS: We enrolled 372 Hispanic women from South Texas’ Cameron and Hidalgo counties with a daughter aged 11–17 who had not received HPV vaccine. INTERVENTION: All participants received an HPV vaccine educational brochure in their preferred language (English or Spanish) and were invited to participate in the Entre Madre e Hija (EMH) program, a culturally relevant cervical cancer prevention program. EMH participants (n= 257) received group health education, referral and navigation support from a promotora (a trained, culturally competent community health worker). Those who declined participation in EMH received the brochure only (n=115). RESULTS: Eighty-four percent of enrolled participants initiated the HPV vaccine, and no differences were observed between EMH program and brochure-only participants. Compared to brochure-only participants, EMH participants were more likely to complete the vaccine series [Adj. OR=2.24, 95% CI (1.25, 4.02)]. In addition, participants who were employed and insured had lower odds of completing the vaccine series [Adj. OR=.45, 95% CI (.21 – .96); Adj. OR=.36, 95% CI (.13 – .98), respectively]. CONCLUSION: All enrolled participants had high vaccine initiation rates (>80%); however, EMH program participants were more likely to complete the vaccine series. HPV vaccine promotion efforts that include referral and navigation support in addition to education show promise.